PERLINDUNGAN HUKUM TERHADAP PENGETAHUAN TRADISIONAL MELALUI PENGEMBANGAN SUI GENERIS LAW - Rohaini Rohaini (Universitas Lampung, 2015)
It’s cannot deny that intellectual property right laws, in certain aspects are possible for using to protect traditional knowledge from their utilization. However, in the same time, intelectuual property rezim also become “a tool” to legitimate of biopiracy practices. Due to the massive of international pressure, mostly developing countries, and the awereness that intellectual property regimes doesn’t optimal to protect traditional knowledge, it develops a discourse to develop a sui generis law outside of intellectual property right regimes. By using the normative method and qualitative approach, this research shows that in order to develop the sui generis law in Indonesia, there are several minimum elements that shall be contained in it, inter alia: the purposes of protection; scope of protection; creteria of protection; the beneficiaries of protection: the holder of traditional knowledge; the kind of rights to be granted; how does the rights acquired; how to enforce it; how does the rights lost or expired; and dispute resolution.Keywords: protection, traditional knowledge, sui generis law